Relacje nauki i społeczności lokalnej na przykładzie zrealizowanych projektów = Relations between science and the local community on the example of completed projects - Baron-Polańczyk, Eunika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article briefly describes selected hybrid educational methods based on ICT and building competences and relations in a learning group, embedded in the theory of constructivism. They are blended learning, experience based learning, interdisciplinary education based on the idea of STEM/STEAM. These methods gained particular importance in the era of the Covid-19 pandemic, because their implementation conditioned the functioning of the education system.
Keywords: edukacja mieszana; uczenie się przez doświadczanie; cykl Kolba; STEAM; projekty edukacyjne; społeczność lokalna; blended learning; experience based learning; Kolb`s cycle; educational projects; local community